EXPLORING THE MULTIFACETED INTERACTIONS BETWEEN MICROBES AND PLANTS FOR ENHANCING PLANT HEALTH, COMBATTING DISEASES, AND MITIGATING ABIOTIC STRESS - SALEEM, U; NOFAL, M; SADDAM, S; FATIMA, R; MUSHTAQ, I; ULLAH, S; KHALID, MN; SHAHEEN, A; KAUSAR, R; AHMAD, MI (Biological and Clinical Sciences Research Journal, 2024)
Arbuscular mycorrhizal fungi (AMFs) are highlighted for their beneficial effects on plant development and stress tolerance. Plant-growth-promoting microorganisms (PGPMs), including various bacterial and fungal species, are identified as key players in enhancing plant growth, nutrient absorption, and disease resistance. The interactions between plants and soil microbes, such as nutrient mobilization and disease prevention, are explored in detail. The article emphasizes the importance of understanding plant-microbe interactions for developing sustainable agricultural practices. It discusses the potential of beneficial microorganisms, such as biological control agents (BCA) and plant-growth-promoting rhizobacteria (PGPR), in improving crop productivity and disease management. The molecular mechanisms underlying plant defense responses and microbial interactions are investigated to develop innovative crop protection strategies. Furthermore, the review article delves into the role of microorganisms in mitigating abiotic stresses, such as salt, drought, and pollution. Plant Growth Promoting Bacteria (PGPB) are highlighted for their ability to enhance nutrient absorption, nitrogen fixation, and resistance to salt stress through induced systemic tolerance (IST). Phytoremediation techniques, which utilize bacteria coexisting with plants to remove organic contaminants and heavy metals from soils, are also discussed. Overall, the review article underscores the significance of plant-microbe interactions in agriculture and environmental remediation. It calls for further research to elucidate the complex mechanisms underlying these interactions and to develop effective strategies for harnessing the potential of beneficial microorganisms in promoting plant growth, nutrient uptake, and stress tolerance.